PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI DENGAN MEDIA VISUAL GAMBAR SISWA SMK - Agus Setiono; Mhd Isman (STKIP Subang, 2024)
This research aims: (1) to determine the skills in writing procedural texts using the Project Based Learning learning model, (2) to determine the skills in writing descriptive texts using conventional learning models and (3) to determine the influence of the Project Based Learning model in writing descriptive texts. The population in this research were all students in Class The learning model in this research is experimental learning media and the design used is posttest only control design. The findings of data analysis in the conventional learning model class showed that the average student score was 60.60 with a percentage of 74% or 20 students in the score range of 50 - 100 were grouped as low and scored below the KKM. The results of the hypothesis test findings were achieved, the mean of students who used the Project Based Learning model was 84.8 with a percentage of 86% or as many as 28 students in the 80 - 100 range were categorized as high and scored above the KKM. Based on the hypothesis test obtained, the use of the Project Based Learning model is better than the use of conventional learning media and it can be concluded that there is an influence of the Project Based Learning learning model on the skills of writing descriptive texts in Class T.A 2023/2024.